KONVERGENSI SIMBOLIK DALAM KOMUNIKASI KELOMPOK PERSATUAN WARTAWAN INDONESIA (PWI) BANYUMAS - Yulinda Nur Fitriana; Maria Consulata Wening Wijayaningrum; Jeconia Emery Audic; Yunisa Maharani Agustin (QAULAN: Journal of Islamic Communication, 2025)
Professional organizations such as the Indonesian Journalists Association (PWI) are crucial platforms for journalists to build solidarity and collective identity amidst a dynamic media landscape. This study examines the phenomenon of group communication within the PWI Banyumas, a community comprising members from various media institutions that rely on both virtual and face-to-face interactions. The increasing use of digital platforms such as WhatsApp and Zoom groups in daily communication has given rise to unique dynamics that are interesting to analyze through Symbolic Convergence Theory. Communication conducted virtually has several barriers to group communication, and symbolic convergence is explored in this study. The purpose of this paper is to explain the concept of symbolic convergence in group communication within the Indonesian Journalists Association (PWI) Banyumas. This study employs a qualitative descriptive approach, with the PWI Banyumas group serving as the research object. The data collection technique for this study was through group chat observation and direct interaction. Based on the results of this study, it was found that the fantasy theme within the PWI Banyumas group was achieved established through discussions about news and what news to write, as well as jokes that made each member feel considered and comfortable, resulting in a solid conversation with repetition in their interactions. The journalists who join aim to build cohesiveness and assume responsibility for their status and role within the Banyumas PWI group.